Controlled Release Matrix Formulation of Paliperidone in Concurrence with Regulatory Requirements (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Paliperidone is the 9-hydroxy metabolite (9-hydroxy) of risperidone and is a psychotropic drug of the atypical antipsychotic family. Paliperidone has the racemates (+)- and (-)-paliperidone. It is a dopamine D2 antagonist with serotonergic 5-HT2A antagonistic action that acts centrally. ALZA OROS® osmotic medication release technology is used to create Invega ER tablets. It is a tri-layer longitudinally compressed tablet based on a sophisticated osmotic delivery method that is meant to administer the paliperidone in a defined way over 24 hours. This research aims to create a generic controlled-release single-layer matrix tablet of paliperidone. Different combinations of Polyox and hypromellose in the core were used, followed by coating, to assist/build a stable and strong formulation. All strengths have similar in-vitro dissolution profiles. Freeze formulation was assessed for nitrosamine risk assessment as well as challenge for alcohol dose dumping study. Paliperidone is a basic compound with a pKa1 of 8.2 (piperidine moiety) and a pKa2 of 2.6 (pyrimidine moiety). As a result, a substantial portion of the molecule is ionized at physiological pH. It is relatively insoluble in water (0.003 g/100 mL water at pH 7.4). The solubility decreases at higher pH (0.001 g/100 mL at pH 12.9) and significantly increases at lower pH (3 g/100 mL at pH 5.3). The partition coefficient octanol/water (log P) is 2.39. Hence, discriminating media was identified as pH 2.75 buffer. The Higuchi model was used for expressing the in-vitro release profile through matrix composition. Formulation withstands 0–40% alcoholic conditions under in-vitro release tests. It is easy to formulate, stable and cost-effective. The manufacturing process involves dry blending followed by compression and coating so there will be the least chemical interaction of an active substance with other excipients. Hence, there is a negligible possibility to generate nitrosamine impurity in the formulation. The formulation is classified as rugged against dose dumping.